Ageing perceptions and non-adherence to aromatase inhibitors among breast cancer survivors. (March 2018) - Brier, Moriah J.; Chambless, Dianne L.; Chen, Jinbo; Mao, Jun J.
Abstract: Purpose: Aromatase inhibitors (AIs) are a potentially life-saving treatment for breast cancer survivors, yet poor adherence to treatment is a prevalent problem. A common adverse effect of AI treatment is arthralgia, which is identified by survivors as a major reason for treatment discontinuation. Women who experience arthralgia on AIs often report feeling they have aged rapidly while on the treatment. In the present study, we examined whether arthralgia-associated ageing perceptions predicted non-adherence. Patients and methods: We conducted a prospective cohort study among women with stage I–III breast cancer, who were on an AI and completed the Penn Arthralgia Aging Scale within 2 years of AI initiation. Adherence data were abstracted from medical charts by trained raters. Cox proportional hazard analysis was used to determine the relationship between ageing perceptions and time to non-adherence. All analyses included adjustments for joint pain severity. Results: Among 509 participants, 144 (28.3%) were non-adherent. As hypothesised, women with high levels of ageing perceptions were at greater risk of non-adherence than women with low levels of ageing perceptions (adjusted hazard ratio [HR], 1.71; 95% confidence interval [CI], 1.10–2.67; p = .02). High levels of depressive symptoms were also uniquely associated with increased risk of non-adherence (adjusted HR, 1.63; 95% CI, 1.03–2.59; p = .04). Conclusion: Perceptions of ageing related to arthralgia and depressive symptoms predicted non-adherence to AIs. These findings suggest that interventions that address negative beliefs about ageing due to AI-related arthralgia and depressive mood can potentially improve rates of adherence to AIs. Highlights: Many breast cancer survivors on aromatase inhibitors (AIs) who experience joint pain feel a sense of accelerated ageing. We demonstrate that heightened perceptions of ageing predicts non-adherence to AIs, after controlling for joint pain. AI-related ageing perceptions are potentially modifiable and can be targeted in interventions to improve adherence to AIs.